2021
DOI: 10.3389/fgene.2021.646929
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and Copy Number Alterations Analysis of KIF23 in Glioma

Abstract: In glioma, kinesin family member 23 (KIF23) is up-regulated and plays a vital role in oncogenesis. However, the mechanism underlying KIF23 overexpression in malignant glioma remains to be elucidated. This study aims to find potential causes of KIF23 high expression at genome level. To clarify this issue, we obtained point mutation and copy number alterations (CNAs) of KIF23 in 319 gliomas using whole-exome sequencing. Only two glioma samples with missense mutations in KIF23 coding region were identified, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The best explanation is that diffuse astrocytic and oligodendroglial tumors are classified by the presence of isocitrate dehydrogenase 1 or 2 (IDH1/2) mutation in the 2016 World Health Organization (WHO) classification of central nervous system (CNS) tumors for the impact of specific gene mutations on the progression and patient outcome of glioma [ 64 ]. In addition, Zhao et al found that after the copy number of KIF23 alterations, its expression level is increased, which in turn leads to tumorigenesis and the development of gliomas [ 65 ]. Our experimental results showed that the TRIM family molecules are genetically altered in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…The best explanation is that diffuse astrocytic and oligodendroglial tumors are classified by the presence of isocitrate dehydrogenase 1 or 2 (IDH1/2) mutation in the 2016 World Health Organization (WHO) classification of central nervous system (CNS) tumors for the impact of specific gene mutations on the progression and patient outcome of glioma [ 64 ]. In addition, Zhao et al found that after the copy number of KIF23 alterations, its expression level is increased, which in turn leads to tumorigenesis and the development of gliomas [ 65 ]. Our experimental results showed that the TRIM family molecules are genetically altered in gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…KIF23 was first found in 1992, which was a plus-end-directed motor enzyme. 30 Studies have suggested KIF23 as a potential biomarker in several tumors. 31 KIF23 promoted gastric carcinogenesis by activating Wnt/β-Catenin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…By serving as a bridge between recycling vesicles and the microtubule network through its connection with STX4 and SNAP25, it controls the recycling of the plasma membrane. including gastric, esophageal, liver, colorectal, pancreatic, 57,59,60 cervical, prostate, ovarian, bladder, 60,61 lung, gliomas, 62 lymphoma, melanoma, and in BC. 60,63 KIF23 promotes cancer cell proliferation via direct competitive interaction with the membrane recruitment protein 1 (Amer1), blocking the association of this protein with the adenomatous polyposis coli (APC), thereby relocating Amer1 from the membrane and cytoplasm to the nucleus and attenuating its ability to negatively regulate Wnt/β-catenin signaling, thus activating this signaling pathway.…”
Section: Cenpfmentioning
confidence: 99%